Preschool English Foreign Language Vocabulary Test (PEVOT) for ESL Training in Costa Rica - García-Castro, Verónica (2025)
Vocabulary tests that match national curricula tend to be more suitable to the academic and social setting of students (Nikolov & Timpe-Laughlin, 2021). However, certain countries with limited educational budgets, such as Costa Rica (State of the Nation Report, 2021) may prioritize other areas, such as basic infrastructure or literacy, over developing and implementing standardized vocabulary assessments. This shortcoming was addressed in a descriptive study that used an innovative curriculum-based test to assess and explore English Foreign Language (EFL) vocabulary knowledge among Costa Rican school children. Participants included 128 (Mage=5, SD=6.8 months), students from rural and urban public schools. The methodology included a thorough analysis of the Ministry of Education (MEP) EFL preschool curriculum, followed by the design, piloting, and administration of a vocabulary test in English. The findings revealed that children of all ages are capable of recognizing EFL vocabulary included in the  current EFL program at the Costa Rican Ministry of Education. However, urban public school students demonstrated a significantly higher academic performance than students from rural public schools.  The study concludes that EFL testing is an effective method in assessing preschool student EFL vocabulary knowledge. The study also considers shortcomings and future recommendations.